Aquaculture in transition: Value chain transformation, fish and food security in Myanmar - Belton, Ben; Hein, Aung; Htoo, Kyan; Kham, L. Seng; Nischan, Ulrike; Reardon, Thomas; Boughton, Duncan (Michigan State University, 2015)
Fish farming (aquaculture) is important to Myanmar’s food security and is developing and transforming quickly. This study presents findings from a new field survey of the farmed fish value chain that is more detailed and broader than any previous study conducted in Myanmar. Many of our findings are at odds with what we perceive as conventional wisdom about fish farming in Myanmar. The findings have important policy implications to unlock the sector’s full growth potential and food security contributions.